2004
DOI: 10.1111/j.1365-2486.2004.00833.x
|View full text |Cite
|
Sign up to set email alerts
|

C3 grasses have higher nutritional quality than C4 grasses under ambient and elevated atmospheric CO2

Abstract: Grasses with the C 3 photosynthetic pathway are commonly considered to be more nutritious host plants than C 4 grasses, but the nutritional quality of C 3 grasses is also more greatly impacted by elevated atmospheric CO 2 than is that of C 4 grasses; C 3 grasses produce greater amounts of nonstructural carbohydrates and have greater declines in their nitrogen content than do C 4 grasses under elevated CO 2 . Will C 3 grasses remain nutritionally superior to C 4 grasses under elevated CO 2 levels? We addressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
131
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(141 citation statements)
references
References 62 publications
6
131
2
2
Order By: Relevance
“…Several studies reported that the nutritional quality and/or digestibility of C4 species is inferior to that of C3 species (e.g., Sponheimer et al, 2003b;Barbehenn et al, 2004) although the opposite was also reported (Scheirs et al, 2000). Digestibility decreases strongly with age of plant material (Fick et al, 1994).…”
Section: Isotopic Shift Between Vegetation and Woolmentioning
confidence: 88%
“…Several studies reported that the nutritional quality and/or digestibility of C4 species is inferior to that of C3 species (e.g., Sponheimer et al, 2003b;Barbehenn et al, 2004) although the opposite was also reported (Scheirs et al, 2000). Digestibility decreases strongly with age of plant material (Fick et al, 1994).…”
Section: Isotopic Shift Between Vegetation and Woolmentioning
confidence: 88%
“…In native pastures this was mostly due to the increased dominance of C 4 grasses, which are nutritionally inferior to C 3 grasses, even at elevated [CO 2 ], due to their lower protein content (Barbehenn et al 2004). Rising [CO 2 ] has also been shown to lead to decreased protein and N contents of a variety of species across a range of temperatures (Zvereva & Kozlov 2006, Taub et al 2008, further reducing pasture quality.…”
Section: Discussionmentioning
confidence: 99%
“…3), leading to a substantial change in species composition. Since C 3 species are expected to have higher forage quality than C 4 species at elevated CO 2 concentrations, despite some changes in protein and carbohydrate levels (Barbehenn et al 2004), this shift towards C 4 dominance could reduce forage quality, lowering ruminant animal production and increasing methane emissions (Howden et al 2008).…”
Section: Responses To Climate Change Scenariosmentioning
confidence: 99%
“…In most cases, C 3 species are of higher forage quality than C 4 species, and are expected to remain so under elevated atmospheric CO 2 conditions (Barbehenn et al 2004), so the effect of climatic change on the balance between C 3 and C 4 species could have important implications for animal production. In addition, changes to rainfall patterns may influence natural resource degradation processes such as erosion and salinity through changes in runoff and drainage patterns (van Ittersum et al 2003;Howden et al 2008).…”
Section: Introductionmentioning
confidence: 99%